Poly-β-(1→6)-N-acetyl-D-glucosamine mediates surface attachment, biofilm formation, and biocide resistance in Cutibacterium acnes - Kaplan, Jeffrey B.; Cywes-Bentley, Colette; Pier, Gerald B.; Yakandawala, Nandadeva; Sailer, Miloslav; Edwards, Marc S.; Kridin, Khalaf (Frontiers in Microbiology, 2024)
The commensal skin bacterium Cutibacterium acnes plays a role in the pathogenesis of acne vulgaris and also causes opportunistic infections of implanted medical devices due to its ability to form biofilms on biomaterial surfaces. Here we show that C. acnes produces poly-b-(1®6)-N-acetyl-D-glucosamine (PNAG), an extracellular polysaccharide that mediates biofilm formation, antimicrobial resistance, host colonization, immune evasion, and stress tolerance in a wide range of bacterial pathogens. PNAG was detected by fluorescence confocal microscopy on the surface of C. acnes cells using the antigen-specific human IgG1 monoclonal antibody F598. We also found that dispersin B, a PNAG-specific glycoside hydrolase, inhibited attachment of C. acnes cells to polystyrene rods and biofilm formation by C. acnes in glass and polypropylene tubes. Dispersin B also sensitized C. acnes biofilms to killing by benzoyl peroxide and tetracycline. PNAG may play an important role in C. acnes biofilm formation, skin colonization, biocide resistance, and virulence.Cutibacterium acnes is a bacterium that is found on the skin of most people. C. acnes helps maintain a healthy skin microbiota but also causes acne and infections of implanted medical devices. In this study we found that C. acnes produces an adhesive extracellular polysaccharide named PNAG (poly-N-acetylglucosamine) which may help C. acnes colonize skin and medical implants. We found that PNAG protects C. acnes from killing by benzoyl peroxide and tetracycline, two drugs that are commonly used to treat acne. PNAG may represent a novel target for skin antiseptics and anti-acne drugs.